Comparison of Microleakage between Endodontic Temporary Restorative Materials Placed at Different Times - M Zare Jahromi; M Khabiri; Z Hashemzadeh (Isfahan University of Medical Sciences, 2007)
Introduction: The aim of this study was to compare the sealing ability of two temporary restorative materials, Cavit and Coltosol, in different times by dye penetration method.Methods and materials: 70 extracted human anterior teeth were collected. Standard access cavities were prepared and then teeth cleaning until 40 and shaping until 70 were done. The canals were then obdurate with gutta percha and A.H 26 sealer. Samples were divided into five groups: three experimental groups (20 in each one) and two positive and negative control groups (5 in each one). Access cavities were prepared in experimental and positive control groups and pulp chambers were completely excavated. Access cavities of experimental groups were sealed by one particular material using incremental method; but positive control teeth were not sealed. Then all groups were kept in incubator at 37°C; first group for 1 day, second group for 1 week, and third group for 1 month. After this time, all groups were immersed in blue-metylen separately. Then the liner extent of dye penetration was measured. Results were analyzed by one-way analysis of varance. Result: There was statistically significant differences in leakage between all groups at different times (p value < 0.001).Conclusion: Coltosol was found to exhibit better seal comparing cavit. Microleakage will be increased by time.Keywords: Coronal microleakage, temporary restoratives, Cavit, Coltosol